Thermal decomposition of microcrystalline cellulose and its pure and containing adsorbed cadmium cations derivatives. - Chahud, M.; Ionashiro, Massao [UNESP]; Moreira, J. C.; Campos, JTD (Editora Unesp, 1996)
We have studied the thermal decomposition of the microcrystalline cellulose and some of its derivative such as pure carboxymethylcellulose (CMCH), phosphate cellulose (FOSCEL) and oxycellulose (OXICEL) and also these same derivatives containing adsorbed cadmium cations. We have used the TG,DTG tecniques in order to determine the quantity of retained cadmium II cations on the surface of these adsorbents.
Keywords: thermal decomposition; cadmium II adsorption; cellulase and modified cellulose